Madhyayugara Asamīẏā carita puthi sāhitya - Nātha, Mitālī (Pūrbāẏaṇa Prakāśana, 2023)
Research based book on Assamese historical literature; with special reference of 'Charit Puthi', biographical narration of Vaishnavite saints of Assam, India.
Literaturverzeichnis: Seite 157-160
Keywords: Assamese literature; History and criticism.; Vaishnavism in literature.; Vaishnavites; India; Assam; Biography.